2018
DOI: 10.1111/jocn.14354
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the fundamentals of care framework in baccalaureate nursing education: An example from a nursing school in Denmark

Abstract: Integrating the Fundamentals of Care framework can support nursing students' critical thinking and reflection on what fundamental nursing care is and requires and eventually educate nurses in providing evidence-based fundamental nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It may even be necessary to address certain concepts from the beginning of the training so that the participants will concretely integrate the three dimensions into their learning. Several strategies to develop Fundamentals of Care and to implement the FOC framework in baccalaureate nursing education have been tried (Feo, Donnelly, Frensham, Conroy, & Kitson, ; Jangland et al, ; Voldbjerg et al, ). Of course, these attempts will be carefully considered for the development of training strategies based on the FOC‐PP.…”
Section: Methodsmentioning
confidence: 99%
“…It may even be necessary to address certain concepts from the beginning of the training so that the participants will concretely integrate the three dimensions into their learning. Several strategies to develop Fundamentals of Care and to implement the FOC framework in baccalaureate nursing education have been tried (Feo, Donnelly, Frensham, Conroy, & Kitson, ; Jangland et al, ; Voldbjerg et al, ). Of course, these attempts will be carefully considered for the development of training strategies based on the FOC‐PP.…”
Section: Methodsmentioning
confidence: 99%
“…Their results demonstrated that students face challenges in identifying a patient's care needs. Although Feo, Donnelly, et al () and Voldbjerg et al () described and discussed the process of embedding fundamental care within nursing curricula, Jangland et al () presented the initiatives taken to integrate the fundamentals of care framework into a baccalaureate nursing education. Moreover, the results from a pilot study conducted by Alderman et al () offered a practical and feasible way to explicitly embed the fundamentals of care into nursing curricula.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing education plays a vital role in responding to the challenges in nursing care by preparing future nurses to work in a highly specialised healthcare system while meeting the patients’ fundamental care needs (Feo, Frensham, Conroy, & Kitson, ). To regain focus on fundamental nursing care, the faculty and leadership at the School of Nursing at University College, Nordjylland, decided in 2016 to integrate the conceptual Fundamentals of Care framework (FoC) (Figures and ) (Kitson, Conroy, Kuluski, Locock, & Lyons, ) in lectures, case‐based work and simulation laboratories (Voldbjerg et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The framework was developed to give nurses a shared framework for discussing and reflecting on nursing and to put nursing and its complexity back on the agenda in order to meet patients’ needs (Kitson et al, ). The framework has been integrated in case‐based work in nursing education as a tool to support nursing students’ reflexivity and ability to analyse, investigate and reflect on nursing care and develop their understanding of fundamental nursing care (Voldbjerg et al, ). Case‐based work as pedagogical method has shown to stimulate student reflexivity (Thistle Thwaite et al, ) and offers a patient‐centred frame where the FoC framework can draw attention to nursing issues related to fundamental care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation